Learning Organization Practices: A Comparative Study Between Multinationals And Local Companies - Sing, Soo Kian (2002)
The research survey was conducted in Klang valley involving six organizations from hi-tech manufacturing and service industry. This study examines and evaluates learning organizations practices and behaviors of these organizations. The analytical framework of this study is largely based on Watkins and Marsicks (1993), Marquardt (1996) and Peter Senge (1990) conceptual model of learning organization. This research used the questionnaire survey method; and applied descriptive analysis, regression analysis, independent sample t-test and ANOVA analysis to explore retations among variables.